NEODESENVOLVIMENTISMO E COMUNIDADES QUILOMBOLAS: uma questão ausente? - Josiane Cristina Cardoso da Silva (Universidade Federal do Maranhão, 2013)
This article analyzes the impacts of neo-developmentism in the Brazilian countryside and the peasantry, particularly the maroon communities. It discusses how capitalism and neo-developmentism are characterizing the agrarian question in Brazil. It Investigates the social issue and (un) territorialization from this conjecture.